Elevated Serum Uric Acid Levels Are Related to Cognitive Deterioration in an Elderly Japanese Population - Kazushi Suzuki; Daisuke Koide; Kurumi Fujii; Tsutomu Yamazaki; Shoji Tsuji; Atsushi Iwata (Dementia and Geriatric Cognitive Disorders Extra, 2016)
Aims: The association between serum uric acid (UA) levels and cognitive function is controversial since UA can be a risk factor for cerebral ischemia as well as acting as a neuroprotective antioxidant. Methods: We conducted a cross-sectional analysis of 228 elderly participants and examined neuropsychological test results, clinical data as well as brain magnetic resonance imaging data. Patients: Overall, 64 participants were diagnosed with cognitive deterioration. To control for the effect of sex differences, 2 independent sets of single-variable and multivariate logistic regression analyses were performed with quartiles divided into non-sex-specific and sex-specific cutoff values for UA. Results: In non-sex-specific quartiles, the participants in the highest quartiles of UA levels were found to be at a significantly higher risk of cognitive deterioration than those in the lowest quartiles. In sex-specific quartiles, the highest quartile showed an increased risk of cognitive deterioration, and a greater than fourfold increase in the risk in the highest quartiles was confirmed using multivariate regression models. However, no significant association was observed between serum UA levels and the presence of white matter lesions. Conclusions: Elevated serum UA levels were independently associated with cognitive deterioration. UA might have unknown adverse effects on cognitive function, other than causing vascular pathology.